Descriptions of skate egg cases (Chondrichthyes: Rajiformes: Rajoidei) from the eastern North Pacific - Ebert, David A.; Davis, Chante D. (Zootaxa, 2007)
Egg cases for 10 of 11 valid skate species known to occur in the eastern North Pacific (ENP) were identified and are here described. In addition, egg cases of two unidentified skate species were collected from very deep water off central and southern California, USA. Examples of egg cases for all species, except for two, were removed in utero in order to confirm their species specific identification. The egg cases of seven skate species, including egg cases from the two unidentified species, have not previously been described or illustrated from this region. Previous attempts to identify skate egg cases with their associated species have been inadequate. The ENP skate egg cases can broadly be classified into two main groups: those with broad lateral keels (> 10% maximum egg case width) and those with narrow lateral keels (< 10% maximum egg case width). Egg cases in the former group (with broad lateral keels) generally have a finely striated surface texture that is smooth to the touch. Those in the latter group (with narrow lateral keels), with one exception, tend to have a coarse surface texture, often with prickles, and are rough to the touch. A revised key to the skate egg cases from the ENP is provided.